'Florida Brilliance' Strawberry - Vance M. Whitaker; Natalia A. Peres; Shinsuke Agehara (EDIS)
‘Florida Brilliance’ (PPAF) is a new short-day strawberry cultivar released by the University of Florida and commercialized in 2018. This cultivar was originally evaluated as breeding selection FL 13.26-134. It originated from a 2013 cross between breeding selection FL 11.31-14 (female parent) and selection FL 10-153 (male parent). ‘Florida Brilliance’ has been tested over several years at the University of Florida Gulf Coast Research and Education Center (GCREC) in Wimauma, FL, at the Florida Strawberry Growers Association (FSGA) headquarters in Dover, FL, and on several commercial farms.